2019
DOI: 10.1242/jeb.184689
|View full text |Cite
|
Sign up to set email alerts
|

Using on-board sound recordings to infer behaviour of free-moving wild animals

Abstract: Technological advances in the last 20 years have enabled researchers to develop increasingly sophisticated miniature devices (tags) that record an animal's behaviour not from an observational, external viewpoint, but directly on the animals themselves. So far, behavioural research with these tags has mostly been conducted using movement or acceleration data. But on-board audio recordings have become more and more common following pioneering work in marine mammal research. The first questions that come to mind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 147 publications
0
14
0
Order By: Relevance
“…The social learning literature has mainly focused on fear learning in rodents 17,73,74 or spatial task learning in many species 5,13,29,30,[75][76][77] , in which visual cues are presumed to play a central role. However, auditory cues permit animals to accurately localize a conspecific or another species [78][79][80][81][82][83][84][85][86][87] , even when the target is not visible. Here, we found that, in the absence of one modality of information, gerbils can still capitalize on the remaining information Stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The social learning literature has mainly focused on fear learning in rodents 17,73,74 or spatial task learning in many species 5,13,29,30,[75][76][77] , in which visual cues are presumed to play a central role. However, auditory cues permit animals to accurately localize a conspecific or another species [78][79][80][81][82][83][84][85][86][87] , even when the target is not visible. Here, we found that, in the absence of one modality of information, gerbils can still capitalize on the remaining information Stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, animal‐borne accelerometers allow singing activity to be unambiguously attributed to the focal animal. Even when using animal‐borne microphones, it can be challenging to discriminate the vocalizations of the focal individual from those of nearby conspecifics (Anisimov et al, 2014; Gill et al, 2015; Greif & Yovel, 2019); and stationary microphones may only record individuals when they vocalize sufficiently close to the recorder. Recent studies have used autonomous, bioacoustic recorders to monitor vocal activity of nightjars at specific sites (Zwart et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is possible that apparent cases of silence were simply a failure of the microphones to detect the low-intensity and directional micro calls. To overcome these limitations, we attached miniature (2.9 g) ultrasound and acceleration recording devices (“tags”; 16 , 17 ) to wild, freely behaving male hoary bats (females were only rarely captured at our field location and were not available for tag deployments). Bats were captured at the same time of year (autumn) and location (Humboldt Redwoods State Park, California) as the previous study 14 , allowing us to compare results between on-board and ground-based recording methods.…”
Section: Introductionmentioning
confidence: 99%